Stephen Luis Vilaseca. Barcelonan Okupas: Squatter Power! Madison: Fairleigh Dickinson UP, 2013. - Enric Bou (Studies in 20th & 21st Century Literature, 2017)
Review of Stephen Luis Vilaseca. Barcelonan Okupas: Squatter Power!. Madison/Teaneck: Fairleigh Dickinson UP, 2013.
Keywords: Review; Stephen Luis Vilaseca; Barcelonan Okupas: Squatter Power!; Enric Bou